Means, methods and results of training control in combat sports - Tünnemann, H. (1999)
1.Theoretical approach to training and performance control in combat sports 2.Computer and video based methods and procedures of competition analysis 3.Performance diagnostical procedures to control conditional performance capacity 4.Training with measuring and information systems as an effective way to control performance in combat sports 5.Multimedia concept for the development of an efficient communication in combat sports 6.References